PENINGKATAN KEMAMPUAN MENGGUNAKAN EJAAN DAN TANDA BACA DALAM MENULIS PENGALAMAN PRIBADI DENGAN TEKNIK JIGSAW SISWA KELAS VII-B SMP NEGERI 1 RENGEL KABUPATEN TUBAN - Kustomo, Heri (Paramasastra, 2015)
The  research  problem  is  the  low  ability  students  at  class  VII-B  SMP  Negeri  1 Rengel Tuban in using spelling and punctuation to write personal experience. It is seen  from  the  data:  1)  errors  capitalization  89.65%,  2) misuse  of  prepositions 86.20%, 3) misapplication dot 75.86%, and 4) error use commas 41.37% .  Researchers  chose  Jigsaw  technique  to  overcome  the  problems.  This  selection was  based  on  the  advantages  of  Jigsaw  technique  is  to  learn  together,  the problems faced by students can be resolved. Results of  the study: There was an  increase  in  the ability  to use correct spelling and  punctuation  in writing  personal  experience  of  students  of  class VII-B  SMP Negeri  1  Rengel  Tuban,  namely:  1)  errors  capitalization  decreased  by  41.38% from  82.75%  to  41,  37%,  2) misuse  of  prepositions  decreased  by  13.80%  from 79.31%  to  65.51%,  and  3)  the  use  of  punctuation  errors  decreased  by  75.86% from 82.75% to 6.89 %